2019
DOI: 10.1371/journal.pone.0224071
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of miRNA landscape and cellular networking pathways in stage-specific prostate cancer

Abstract: Dysregulation of miRNAs has been demonstrated in several human malignancies including prostate cancer. Due to tissue limitation and variable disease progression, stage-specific miRNAs changes in prostate cancer is unknown. Using chip-based microarray, we investigated global miRNA expression in human prostate cancer LNCaP, PC3, DU145 and 22Rv1 cells representing early-stage, advanced-stage and castration resistant prostate cancer in comparison with normal prostate epithelial cells. A total of 292 miRNAs were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…The oncogenic activity of miR-181a has been functionally linked to the suppression of the Smad repressor TGIF2 and to the promotion of the EMT process in PCa cells [53]. More recently, according to the hypothesis that miR-181a acts as oncomiR, it has been shown that miR-181a is up-regulated in advanced stages of prostate cancer and it is involved in drug resistance [81].…”
Section: Prostate Cancer (Pca)mentioning
confidence: 99%
“…The oncogenic activity of miR-181a has been functionally linked to the suppression of the Smad repressor TGIF2 and to the promotion of the EMT process in PCa cells [53]. More recently, according to the hypothesis that miR-181a acts as oncomiR, it has been shown that miR-181a is up-regulated in advanced stages of prostate cancer and it is involved in drug resistance [81].…”
Section: Prostate Cancer (Pca)mentioning
confidence: 99%
“…9,20 Our data are in line with other reports showing altered miRNA profiles in multiple pathological conditions with the majority of miRNAs being decreased. [21][22][23][24] Combined miRNA-seq -mRNA-seq analysis for targets of down-regulated miRNAs in PLDC identified the cell cycle, autophagy, cAMP-mediated signaling and cell proliferation as four most affected pathways. All of these pathways play a critical role in J o u r n a l P r e -p r o o f hepatic cystogenesis and have been considered for therapeutic interventions in PLD.…”
Section: Discussionmentioning
confidence: 99%
“…PDGF (involved in EMT) and other growth factors regulate miR-200 expression, while miR-200c directly influences the EGFR and TGF-β receptor signaling [202][203][204]. miR-200b seems significantly downregulated in castration-resistant PCs: miR-200 influences Notch1 expression, and together they regulate EMT progression [205]. miR-200c expression is negatively regulated by ERG in PC cells lines [206].…”
Section: Discussionmentioning
confidence: 99%